Synergia edukacji artystycznej i rozwoju inteligencji emocjonalnej ucznia. Zarys problemu = The synergy of artistic education and the development of emotional intelligence of a student. Outline of the problem - Pasterniak-Kobyłecka, Ewa (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Art is a symbolic culture category that exerts a special influence on the multifaceted development of human beings, their dreams and fascinations. At the beginning of 21st century young generation`s artistic preferences are mainly focused on the easily received and entertaining popular culture.
Keywords: sztuka; edukacja artystyczna; wychowanie estestyczne; wartości; emocje; inteligencja emocjonalna; art; art education; aesthetic education; values; emotions; emotional intelligence